2018
DOI: 10.1021/acsaem.8b00638
|View full text |Cite
|
Sign up to set email alerts
|

Using a Metal Oxide Nanoparticle Interlayer To Efficiently Anchor Polysulfides at High Mass Loading S-Cathodes in Li–S Rechargeable Battery

Abstract: The bulk of the work related to a Li–S rechargeable battery revolves around materials design strategies of a suitable carbon­(/noncarbon)–host matrix targeted toward the entrapment of sulfur and prevention of leaching out of polysulfides into the electrolyte. This strategy, however, limits the extent of sulfur loading and, depending on the host, may simultaneously increase the unutilizable mass of sulfur in the electrode. Recently, usage of interlayers between conventional S|C composite cathode and separator h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Nanostructured metal hydroxides with hydrophilic groups and a functional polar surface have been recently investigated as promising cathode host materials for Li-S batteries, such as Co(OH) 2 nanosheets, 390 Ni(OH) 2 nanoparticles, 125,391,392 Ni(OH) 2 hollow spheres, 393 Ni 3 (NO 3 ) 2 (OH) 4 shells, 394 layered double hydroxides, 395,396 and so on. In 2015, Nie et al reported Co(OH) 2 nanosheets as a conceptually new metal-containing nanostructured material to obstruct the LiPS shuttling and prolong the service life of Li-S cells.…”
Section: Metal Hydroxidesmentioning
confidence: 99%
“…Nanostructured metal hydroxides with hydrophilic groups and a functional polar surface have been recently investigated as promising cathode host materials for Li-S batteries, such as Co(OH) 2 nanosheets, 390 Ni(OH) 2 nanoparticles, 125,391,392 Ni(OH) 2 hollow spheres, 393 Ni 3 (NO 3 ) 2 (OH) 4 shells, 394 layered double hydroxides, 395,396 and so on. In 2015, Nie et al reported Co(OH) 2 nanosheets as a conceptually new metal-containing nanostructured material to obstruct the LiPS shuttling and prolong the service life of Li-S cells.…”
Section: Metal Hydroxidesmentioning
confidence: 99%
“…This was found to be the optimal concentration for the absorbance measurements. The control sample was prepared by dissolving 120 μL of 1 M of LiTFSI and 0.2 M of LiNO 3 in 3 mL of DOL/DME (1:1 v/v), which was further diluted four times . All of the electrolyte preparations and cell disassembly for the present study were carried out in an (MBraun) glovebox with H 2 O and O 2 levels less than 0.5 ppm.…”
Section: Experimental Section: Materials and Methodsmentioning
confidence: 99%
“…With the development of battery technology, extensive attention has been paid to the improvement of safety and energy density. Nowadays, it is difficult to further increase the energy density of commercial lithium-ion battery (LIB) systems, especially concerning the safety issues. Replacing the flammable organic electrolytes with the stable solid electrolytes (SEs) is viewed as one of the most effective ways to improve the energy density and safety because the SEs offer the capability of using the high-specific capacity lithium metal anodes and the high-voltage cathodes. , Furthermore, concerning the achievement of high energy density, cathodes with high mass loading and excellent kinetics are necessary. In previous reports, a large number of electronically and ionically conductive additives were added in the cathodes, which took 20–30 wt % of the total mass of the cathode in order to form a continuous conductive network. This caused reduced occupation of active materials, hindering the improvement of energy density …”
Section: Introductionmentioning
confidence: 99%